Comfortable Architecture Redesigning How We Think About Comfort - Thure Röckemann (Institute for Research and Community Services Udayana University, 2026)
Comfort has been a cornerstone of architectural design, shaping how spaces influence human well-being physically, emotionally, and socially. This paper examines comfort as a dynamic and multidimensional concept, exploring its variations across different climates and the challenges associated with its excessive pursuit, such as isolation, stagnation, and environmental strain. The transformative role of discomfort is highlighted as a means to foster resilience, creativity, and connection. Furthermore, the paper discusses architectural strategies that balance comfort with sustainability, using case studies from tropical, temperate, and arid regions to provide actionable insights for reimagining comfort in the built environment.